Quantum Chemical Calculations (QSAR) of antipyrine drug and its Metabolites - Ibrahim, A.A.; Abdalrazaq, E.A.; Ibrahim, M.A.; Yahya, R.; Sulliman, E.A. (2012)
The electronic properties of antipyrine and its metabolites have been investigated theoretically by the different methods of semi-empirical (AM1, MNDO/3 and PM3) and ab initio at STO-3G level calculations. These metabolites are of much interest due to their biological and medical importance. The charges, HOMO, LUMO, hardness (Î·), electronic chemical potential (Î¼) and global electrophilicity index (Ï) were determined. The metabolites of A4 (according to MNDO/3) and A6 (according to AM1, PM3 and ab initio) have relatively low LUMO-HOMO differences indicating that these compounds would be the most reactive metabolites.